2012
DOI: 10.1016/j.bpj.2012.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Tonotopic Relationships Reveal the Charge Density Varies along the Lateral Wall of Outer Hair Cells

Abstract: Outer hair cells amplify and improve the frequency selectivity of sound within the mammalian cochlea through a sound-evoked receptor potential that induces an electromechanical response in their lateral wall membrane. We experimentally show that the membrane area and linear membrane capacitance of outer hair cells increases exponentially with the electrically evoked voltage-dependent charge movement (Q(T)) and peak membrane capacitance (C(peak)). We determine the size of the different functional regions (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 51 publications
5
42
0
Order By: Relevance
“…To provide amplification within the cochlear partition, the OHC must exert its force fast and at the right time. OHCs can respond to sinusoidal voltage stimulation above 80 kHz (32), and although resistorcapacitor (RC) filtering posed initial skepticism due to expected decreases in eM driving force at high acoustic frequencies (26,50), much work has basically eliminated this concern (14,(51)(52)(53)(54)(55). However, one of those potential mechanisms that we envisioned to overcome the RC problem does not survive tests with our model.…”
Section: Models Of Prestinmentioning
confidence: 97%
“…To provide amplification within the cochlear partition, the OHC must exert its force fast and at the right time. OHCs can respond to sinusoidal voltage stimulation above 80 kHz (32), and although resistorcapacitor (RC) filtering posed initial skepticism due to expected decreases in eM driving force at high acoustic frequencies (26,50), much work has basically eliminated this concern (14,(51)(52)(53)(54)(55). However, one of those potential mechanisms that we envisioned to overcome the RC problem does not survive tests with our model.…”
Section: Models Of Prestinmentioning
confidence: 97%
“…Several mechanisms have been postulated to understand why the RC filter should not interfere with prestin activity at high frequencies. Previously, we envisioned three mechanisms that might help: 1), because turgor pressure within the OHC shifts the voltage dependence of NLC and electromotility (22,29,30), we suggested that alterations in turgor pressure could align V h and resting potential (22); 2), because prestin charge density increases in high-frequency OHCs (31,32), we reasoned that the rising electrical energy delivered to the lateral membrane could counter the reduced voltage drive; and 3), we reasoned that the flux of chloride through the stretch-activated chloride conductance, G metL , in the lateral membrane could gate prestin's chloride-dependent activity independent of the membrane RC (6). Though the first two possibilities remain tenable, the latter is unlikely, because we have recently discovered that the effects of chloride on prestin are low-pass filtered by a slow intermediary state transition (33).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously estimated that mechanical responses at high acoustic frequencies would be markedly smaller than basilar motion, based on the cell's RC time constant. This problem has been addressed by many investigators, and many ostensible resolutions to the RC time-constant problem have been proposed (15,25,(59)(60)(61)(62). However, we must now consider the slow kinetics of prestin at physiological chloride levels that we have uncovered.…”
Section: Frequency Dependence Of Ohc Charge Movementmentioning
confidence: 99%